Application of yeast technology in ruminant nutrition - Swyers, Kelcey L., author; Archibeque, Shawn L., advisor (Colorado State University. Libraries, 2009)
This research aimed to evaluate two types of yeast technology applications that are commercially available to feed in the diets of beef cattle; these two applications are dried distiller's grains with solubles (DDGS) and yeast culture (YC). First, DDGS were offered as a protein and energy supplement to pregnant range cows to evaluate performance, and nitrogen and trace mineral status of cows and calves (Exp. 1), then YC was fed as a natural alternative to an ionophore to heavy-weight yearling beef steers fed finishing diets consisting of 19.7% DDGS to evaluate growth performance, carcass merit, cost of gain (COG) (Exp. 2), and fecal prevalence of the foodborne pathogen, E. coli O157:H7 (Exp. 3). In Exp. 1, supplementing the diets of pregnant beef cows maintained on dormant winter range with DDGS improved cow performance, had limited impact on nitrogen or mineral status, and was more economical to feed than the control diet (standard range cubes). In Exp. 2, we found that feeding YC may improve carcass characteristics of steers finished at lower end weights, which could result in fewer days on feed; however, there was no advantage on growth performance or COG. Lastly, Exp. 3 indicated that feeding YC decreased, but did not eliminate, fecal shedding of E. coli O157:H7 upon initial application.
Keywords: dried distillers grains with solubles; ionophores; ruminants; yeast culture; microbiology; animal sciences